Privacy as Invisibility: Pervasive Surveillance and the Privatization of Peer-to-Peer Systems - Francesca Musiani (tripleC: Communication, Capitalism & Critique)
This article addresses the ongoing, increasing privatization of peer-to-peer (P2P) file sharing systems – the emergence of systems that users may only join by personal, friend-to-friend invitation. It argues that, within P2P systems, privacy is increasingly coinciding with “mere” invisibility vis-à-vis the rest of the Internet ecosystem because of a trend that has shaped the recent history of P2P technology: The alternation between forms of pervasive surveillance of such systems, and reactions by developers and users to such restrictive measures. Yet, it also suggests that the richness of today’s landscape of P2P technology development and use, mainly in the field of Internet-based services, opens up new dimensions to the conceptualization of privacy, and may give room to a more articulate definition of the concept as related to P2P technology; one that includes not only the need of protection from external attacks, and the temporary outcomes of the competition between surveillance and counter-surveillance measures, but also issues such as user empowerment through better control over personal information, reconfiguration of data management practices, and removal of intermediaries in sharing and communication activities.